Asymmetric Catalysis within the Chiral Confined Space of Metal–Organic Architectures. Issue 32 (4th February 2019) - Li, Xuezhao; Wu, Jinguo; He, Cheng; Meng, Qingtao; Duan, Chunying
Abstract: The effective synthesis of chiral compounds in a highly enantioselective manner is obviously attractive. Inspired by the enzymatic reactions that occur in pocket‐like cavities with high efficiency and specificity, chemists are seeking to construct catalysts that mimic this key feature of enzymes. Recent progress in supramolecular coordination chemistry has shown that metal–organic cages (MOCs) and metal–organic frameworks (MOFs) with chiral confined cavities/pores may offer a novel platform for achieving asymmetric catalysis with high enantioselectivity. The inherent chiral confined microenvironment is considered to be analogous to the binding pocket of enzymes, and this pocket promotes enantioselective transformations. This work focuses on the recent advances in MOCs and MOFs with chiral confined spaces for asymmetric catalysis, and each section is separated into two parts based on how the chirality is achieved in these metal–organic architectures. A special emphasis is placed on discussing the relationship between the enantioselectivity and the confined spaces of the chiral functional MOCs and MOFs rather than catalytic chemistry. Finally, current challenges and perspectives are discussed. This work is anticipated to offer researchers insights into the design of sophisticated chiral confined space‐based metal–organic architectures for asymmetric catalysis with high enantioselectivity. Abstract : Supramolecular metal–organic architectures (metal–organic cages and metal–organic frameworks) feature with chiral confined space analogous to the binding pocket of enzymes exhibiting an ideal working yard to accelerate the series of novel asymmetric catalysis. The relationship between the enantioselectivity and chiral confined environment rather than catalytic chemistry is emphasized here.